Stephen Fry in America [videorecording (DVD)] - Davidson, John-Paul; Waldman, Michael; Fry, Stephen, 1957- (BFS Entertainment & Multimedia Ltd., 2010)
British "comic genius, Stephen Fry, travels through each of America's states in his black London taxi to discover, in his own charismatic style, what makes the country unique and to get under the skin of American life"--Container.